The American Convention on Human Rights : crucial rights and their theory and practice / Cecilia Medina Quiroga, Valeska David Contreras. - Medina Quiroga, Cecilia; David Contreras, Valeska (Intersentia, 2022)
The first edition of The American Convention on Human Rights showed the hesitant steps of a court trying to find its way in a region plagued by egregious human rights violations, the absence of democracy and a significant disregard of international human rights norms. The second edition followed this up by introducing an analysis of the advancement in the reasoning of the Court regarding the violations that it had been dealing with since its inception. This third edition contains an updated and in-depth analysis of the norms applied by the Inter-American Court of Human Rights to deal with the most frequent human rights violations that still occur in Latin America regarding life, humane treatment, personal liberty, due process, access to justice, the principle of legality and judicial protection. The second edition contained a chapter on disappearances, as the Court at the time had significantly developed its reasoning on the matter; this third edition shows the latest evolution on the subject, which still plagues the region. In addition, a new chapter examines discrimination, an issue that has emerged as a frequent and important concern in the Court's work. This edition also reflects the dynamic development of the Court's work in recent years, which has evolved to a more refined jurisprudence covering more specific aspects of the rights examined and topics not previously addressed.